Technology-enhanced explicit vocabulary instruction in teaching biology: Improving scientific discourse and performance - Eval, Abigail A. (Animo Repository, 2019)
Students find it hard to articulate the language of science because of various terminologies that they need to remember and comprehend. Their science academic achievement and participation in class discussions are anchored to their deep understanding of science vocabulary. With this, the researcher tested the incorporation of technology-enhanced explicit vocabulary instruction in teaching practices to improve the students’ inquiry/literacy skills and active engagement in learning. Various activities to incorporate vocabulary instruction was used to grade 7 students. This strategy was used by two classes (n=62) in a certain public school in Quezon City. The results of the post-test of the two sections was used to determine if content understanding on the topic on living things other than plants and animals was achieved. The results of class observation on the two classes was used to see if the explicit vocabulary instruction is an effective strategy to boost students’ participation during class discussions.